2002
DOI: 10.1002/jctb.579
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of the bio‐processing of cotton textiles by combined enzyme/ultrasound treatment

Abstract: Utilization of highly speci®c enzymes for various textile-processing applications is becoming increasingly popular because of their ability to replace harsh organic/inorganic chemicals currently used by the textile industry. Thus, a signi®cant decrease in the amount and toxicity of textile wastewater ef¯uents is achievable. It was established that ultrasound does not inactivate the complex structures of enzyme molecules and as a consequence there was signi®cant improvement in the performance of both cellulase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 10 publications
(9 reference statements)
1
21
0
Order By: Relevance
“…The high rate of mass transfer in textile processing steps has been studied as an alternative to conventional methods [59,60]. Yachmenev et al [61] have reported that a combined treatment of enzyme/sonication on cellulosic textiles offers significant advantages such as less consumption of expensive enzymes, shorter processing time, less fiber damage, and better uniformity of treatment. Perelshtein et al [62] successfully produced antibacterial cotton using an ultrasound technique for coating cotton by MgO and Al 2 O 3 nanoparticles.…”
Section: Ultrasound Colorationmentioning
confidence: 99%
“…The high rate of mass transfer in textile processing steps has been studied as an alternative to conventional methods [59,60]. Yachmenev et al [61] have reported that a combined treatment of enzyme/sonication on cellulosic textiles offers significant advantages such as less consumption of expensive enzymes, shorter processing time, less fiber damage, and better uniformity of treatment. Perelshtein et al [62] successfully produced antibacterial cotton using an ultrasound technique for coating cotton by MgO and Al 2 O 3 nanoparticles.…”
Section: Ultrasound Colorationmentioning
confidence: 99%
“…However, efforts have been made to find substitutes for toxic chemicals used in textile processing (Chen & Burns, 2006). Consequently, several new technologies (ozone, ultrasound, ultraviolet and enzymes) or materials have started to be used for reducing the production of waste by-product and air and water pollution (Arumugam, 2005;Lenting & Warmoeskerken, 2004;Moholkar, Nierstrasz, & Warmoeskerken, 2003;Perincek, 2006;Perincek, Bahtiyari, Körlü, & Duran, 2007a, 2008Perincek, Duran, Körlü & Bahtiyari, 2007b;Rogers, Jeon, & Svenson, 2005;Yachmenev, Bertoniere, & Blanchard, 2002;Yachmenev, Blanchard, & Lambert, 2004Perincek et al, 2008.…”
Section: Introductionmentioning
confidence: 98%
“…Research on cotton bioscouring so far has focused on how to overcome this problem. Pretreatments before pectinase scouring-including boiling water [13], beta-cyclodextrin [14] and mechanical piercing [15], and simultaneous processes with pectinase in one bath such as reverse micellar system [16], organic solvent [17] and ultrasound [18][19][20] have been extensively investigated to improve the accessibility of pectinases to the substrates on cotton fibers and some positive results were published. However, these methods almost have some disadvantages to some extent involving special equipments, energy consumption, processing cost, environmental problem and so on.…”
Section: Introductionmentioning
confidence: 99%